Investigations and time trends in loop ileostomy reversals following anterior resections: a single Australian institution seven‐years' experience. Issue 5 (9th December 2020) - Taylor, Danielle; Besson, Alex; Faragher, Ian G.; Chan, Steven T. F.; Yeung, Justin M.
Abstract: Background: Currently no consensus exists regarding what pre‐reversal investigations are required to assess integrity of the rectal anastomosis. The objective of this study was to compare pre‐reversal assessments of anastomotic integrity and to evaluate trends that might have influenced timings for reversal. Methods: From a prospectively maintained database, patients with colorectal cancer resections between March 2012 and October 2019 were identified. Patient characteristics, pre‐reversal contrast enema and flexible sigmoidoscopy findings were recorded, and management of complications were recorded. Time‐to‐ileostomy reversal and time series for trends were analysed. Results: There were 154 patients included. Pre‐reversal contrast enema or sigmoidoscopy detected a possible stricture or leak at the rectal anastomotic site in 11% (15/132) and 15% (18/112), respectively. When both modalities were used there was concordance of 86.1% and a positive likelihood ratio of 5.73. Of 125 (81.2%) ileostomies reversed, the median time‐to‐reversal was 11.99 months; time series analysis over the 7‐year period showed no significant trend for average patient‐days from booking to reversal ( P = 0.60). Cox regression modelling did not identify any influential risk factors for the times taken to reversal. Conclusion: This study supports the use of both contrast enema and flexible sigmoidoscopy in the assessment of rectal anastomosis integrity. Most patients with complications can have their ileostomies reversed. Patients who have adjuvant chemotherapy have a prolonged time to reversal. Abstract : This retrospective study compared the use of both contrast enema and flexible sigmoidoscopy in the assessment of rectal anastomosis integrity, and the timing of ileostomy reversal at one institution over a 7‐year period. We suggest that both investigations should be used prior to ileostomy reversal and that most patients with complications can have their ileostomies safely reversed.